Changes in the Main Characters in the Serial Film I Don’t Hate Rain: A Review of Skinner’s Behaviorism Psychology - Amelia Eka Firnanda; Abdul Aziz Khoiri (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study examines the behavior of the character Karang in the serial film Aku Tak Memenang Hujan using B.F. Skinner’s behaviorist literary psychology approach. This study aims to describe the forms of stimulus, response, and behavioral effects of the character Karang that emerge as a result of interaction with the surrounding environment. The research method used is a descriptive qualitative method with data sources in the form of the serial film Aku Tak Memenang Hujan. The data collection technique is carried out through documentation in the form of screenshots of scene clips containing elements of stimulus, response, and the effects of the character’s behavior. The collected data are then analyzed through the stages of data reduction, data presentation, and conclusion drawing. Based on the results and discussion of the research on the serial film Aku Tak Memenang Hujan using Skinner’s behaviorist psychology theory, three things can be concluded. First, this study has found various forms of stimulus originating from the surrounding environment Karang undergoes a learning process. These stimuli come from the family environment, school, and social environment that influence changes in the behavior of the character Karang. Second, the response shown by the character Karang appears as a direct reaction to the stimulus he receives, whether in the form of an emotional response, a verbal response, or a physical response. Third, the effects of this response impact the behavior and psychological state of Karang’s characters, characterized by the emergence of childhood trauma, internal conflict, and personality disorders.